Assessment of Clinical and Echocardiographic Findings of Pregnant Women with Dyspnea - Tabassum Muzaffar; Sadia Fatima; Hajira Akbar; Nighat Shafique; Tahira Riaz; Rozina Shahid (Pakistan Armed Forces Medical Journal, 2022)
Objective: To measure the frequency of dyspnea in pregnant patients and to evaluate the clinical and echocardiographic findings of pregnant women had dyspnea.